Geomorphic Indicators of Folds Lateral Growth Using Satellite Images: Sulaimaniyah Vicinity in Kurdistan Region of Iraq - Sissakian, Varoujan K.; Abdullah, Lanja H.; Abdulkareem, Balanbo N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Visual interpretation of satellite images is a very significant technique to recognize and interpret structural features, which indicate lateral growth of folds, the origin of folds, and dating of folds using the exposure dating method. In this study, Landsat 8 (ESSRI) and Google Earth images are used to recognize structural features at Pira Magroon, Surdash, and Azmar anticlines in the Sulaimaniyah vicinity, Kurdistan Region, north of Iraq. The mentioned anticlines are outstanding geomorphological and structural features in the Sulaimaniyah vicinity. The recognized and interpreted structural features include: en-echelon folding, domes, and Neotectonic indication. All these features are discussed in detail with many images to show the discussed cases, most of the interpreted data and presented figures are never mentioned previously.